Arsenocholine-O-sulfate: A novel compound as major arsenic species in the parasitic mushroom Tolypocladium ophioglossoides - Braeuer, Simone; Borovička, Jan; Glabonjat, Ronald A; Steiner, Lorenz; Goessler, Walter (Chemosphere, 2021)
The As concentrations, along with 34 other elements, and the As speciation were investigated in wild-grown samples of the parasitic mushroom Tolypocladium ophioglossoides with inductively coupled plasma mass spectrometry (ICPMS) and high performance liquid chromatography coupled to ICPMS. The As concentrations were 0.070-3.44 mg kg-1 dry mass. More remarkable was the As speciation, where up to 56% of the extracted As were found to be an unknown As species, which was marginally retained under anion- and also cation-exchange conditions. After testing several different chromatographic settings, the compound was finally isolated and identified as 2-(sulfoxyethyl) trimethylarsonium ion (in short: arsenocholine-O-sulfate) with high resolution mass spectrometry. The compound was synthesized and further quantified in all investigated samples via ion-pair chromatography coupled to ICPMS. In addition to the high abundance of arsenocholine-O-sulfate in T. ophioglossoides, small amounts of this As species were also detected in one sample of the host mushroom, Elaphomyces asperulus. In a sample of another parasitic mushroom, Ophiocordyceps sinensis, arsenocholine-O-sulfate could not be detected, but the main species was another unknown compound that was oxidized to inorganic As(V) with hydrogen peroxide. This is the first discovery of arsenocholine-O-sulfate in nature. It is possible that it is present in many other organisms, at least in low concentrations, and just has not been detected there yet because of its unusual chromatographic behavior. The existence of arsenocholine-O-sulfate brings up questions again about the biotransformation pathways of As in the environment and the specific behavior of fungi.
Keywords: Hypocreales; Sulfates; Arsenicals; arsen; arsenikové přípravky; Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; Arsenic; Agaricales; Eurotiales; sírany